(untitled) - Karen A. Lemone (Bocaraton, 1992)
Compiler tools; Language design; Scanner generators; Top-Down parser generators; Bottom-Up parser generators; Semantic analysis and attribute grammars; Optimization: Introduction and control flow analysis; Optimization : Data flow analysis...
Keywords: compilers ( computer programs )